The First Entirely 3D-Printed Training Model for Robot-assisted Kidney Transplantation: The RAKT Box - Riccardo Campi; Alessio Pecoraro; Graziano Vignolini; Pietro Spatafora; Arcangelo Sebastianelli; Francesco Sessa; Vincenzo Li Marzi; Angelo Territo; Karel Decaestecker; Alberto Breda; Sergio Serni (European Urology Open Science, 2023)
Background: Robot-assisted kidney transplantation (RAKT) is increasingly performed at selected referral institutions worldwide. However, simulation and proficiency-based progression training frameworks for RAKT are still lacking, making acquisition of the RAKT-specific skill set a critical unmet need for future RAKT surgeons. Objective: To develop and test the RAKT Box, the first entirely 3D-printed, perfused, hyperaccuracy simulator for vascular anastomoses during RAKT. Design, setting and participants: The project was developed in a stepwise fashion by a multidisciplinary team including urologists and bioengineers via an iterative process over a 3-yr period (November 2019–November 2022) using an established methodology. The essential and time-sensitive steps of RAKT were selected by a team of RAKT experts and simulated using the RAKT Box according to the principles of the Vattituki-Medanta technique. The RAKT Box was tested in the operating theatre by an expert RAKT surgeon and independently by four trainees with heterogeneous expertise in robotic surgery and kidney transplantation. Surgical procedure: Simulation of RAKT. Measurements: Video recordings of the trainees’ performance of vascular anastomoses using the RAKT Box were evaluated blind by a senior surgeon according to the Global Evaluative Assessment of Robotic Skills (GEARS) and Assessment of Robotic Console Skills (ARCS) tools. Results and limitations: All participants successfully completed the training session, confirming the technical reliability of the RAKT Box simulator. Tangible differences were observed among the trainees in both anastomosis time and performance metrics. Key limitations of the RAKT Box include lack of simulation of the ureterovesical anastomosis and the need for a robotic platform, specific training instruments, and disposable 3D-printed vessels. Conclusions: The RAKT Box is a reliable educational tool to train novice surgeons in the key steps of RAKT and may represent the first step toward the definition of a structured surgical curriculum in RAKT. Patient summary: We describe the first entirely 3D-printed simulator that allows surgeons to test the key steps of robot-assisted kidney transplantation (RAKT) in a training environment before performing the procedure in patients. The simulator, called the RAKT Box, has been successfully tested by an expert surgeon and four trainees. The results confirm its reliability and potential as an educational tool for training of future RAKT surgeons.